Integration of knowledge theory and practice: The contribution of Budiuzzaman Said Nursi - Md , Yousuf Ali (s.n, 2013)
Integration of knowledge that represents the intellectual and epistemological aspects of Islam is a challenge. In the history of Islam, all prophets gained knowledge through the revelation from the time of Adam until the time of the last prophet Muhammad (peace be upon him). Indeed, the first revelation of the Qu'ran is to read and write and the prophet of Islam continued its process until the revelation of the whole Qu'ran was completed during his lifetime